THE ROLE OF CHARACTER EDUCATION IN SHAPING THE PANCASILA STUDENT PROFILE - Walib Abdullah; Adi Maladona (PT Altin Riset Publishing, 2026)
This study aims to analyze the role of character education in shaping the Pancasila Student Profile among secondary school students. The research employed a qualitative approach with a case study method conducted at a secondary school that has implemented character education programs and the Pancasila Student Profile Strengthening Project (P5). Data were collected through in-depth interviews, observations, and documentation, and were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings indicate that character education is integrated through intracurricular, cocurricular, and daily habituation activities. The P5 program has been shown to contribute significantly to the development of students’ creativity, collaboration, critical thinking, and social awareness. Teachers play an essential role as role models, facilitators, and mentors in instilling character values. The positive impact of character education is evident in the enhancement of the six dimensions of the Pancasila Student Profile, namely noble character, global diversity, cooperation, independence, critical reasoning, and creativity. Nevertheless, the implementation of character education still faces several challenges, such as inconsistent teacher commitment and limited program implementation time. Overall, this study reinforces that character education plays a central role in realizing the Pancasila Student Profile, and its successful implementation is strongly influenced by school support, teacher exemplification, and the sustained development of a positive school culture.